2020
DOI: 10.21203/rs.3.rs-72639/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

G6PD deficiency and severity of COVID19 pneumonia and acute respiratory distress syndrome: tip of the iceberg?

Abstract: The severe pneumonia caused by human coronavirus (hCoV)-SARS-CoV-2 has inflicted heavy causalities, especially among the elderly and those with comorbid illnesses irrespective of age. The high mortality in African Americans and males, in general, raises concern for a possible X-linked mediated process that could affect viral pathogenesis and the immune system. We hypothesized that G6PD, the most common X-linked enzyme deficiency associated with redox status, may have a role in the severity of pneumonia. A retr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
(49 reference statements)
0
5
1
Order By: Relevance
“…On the follow-up, the minimum hemoglobin values were also higher in the G6PDd group, in contrast to the maximum direct bilirubin values, which were lower than those presented by the G6PDn group. These findings diverge from previous studies, which have reported a decreased hemoglobin level, increased blood neutrophils and increased bilirubin in G6PDd patients with COVID-19 [37,55,56]. Analyzing a selected subgroup, one year later, we showed that only one-third of those participants previously classified as deficient were correctly classified, suggesting a G6PD activity modulation during the illness.…”
Section: Discussioncontrasting
confidence: 99%
“…On the follow-up, the minimum hemoglobin values were also higher in the G6PDd group, in contrast to the maximum direct bilirubin values, which were lower than those presented by the G6PDn group. These findings diverge from previous studies, which have reported a decreased hemoglobin level, increased blood neutrophils and increased bilirubin in G6PDd patients with COVID-19 [37,55,56]. Analyzing a selected subgroup, one year later, we showed that only one-third of those participants previously classified as deficient were correctly classified, suggesting a G6PD activity modulation during the illness.…”
Section: Discussioncontrasting
confidence: 99%
“…Several recent studies have supported this model as they established that G6PD deficient individuals, including many African Americans, are more likely to develop COVID-19 critical illness [6,7,[114][115][116]. Moreover, G6PD deficiency was associated with cardiovascular disease, hypertension, liver fibrosis and iron dyshomeostasis, indicating the importance of redox balance in this pathology [117][118][119][120][121].…”
Section: Covid-19 and Acquired Antioxidant Defectsmentioning
confidence: 90%
“…Clinical observations suggest that G6PD deficiency may worsen outcomes following SARS-CoV-2 infection. Hospitalized patients with G6PD deficiency and COVID-19 pneumonia had lower PaO 2 /FiO 2 ratio, longer duration of mechanical ventilation, and reduced hemoglobin level compared with those with normal G6PD [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher mortality rates have also been observed among African American males admitted for COVID-19 pneumonia [ 18 , 19 ]. Potential explanations for such outcomes include the higher frequency of G6PD deficiency in this population, in addition to socioeconomic factors [ 17 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%